CONCEPT OF SHUKRADHATU - Dahake, Kanchan Yashvantrao; Deshmukh, Vineeta (International Journal of Research -GRANTHAALAYAH, 2020)
Shukra Dhatu is one of the seven Dhatus in the body and Shukra is white, pure, excellent Dhatu, which is considered as best among all seven Dhatus. According to many Acharyas of Ayurveda, Garbhotpadana (reproduction) is chief function of Shukra Dhatu and important fact is Shukra Dhatu also shows its effect all over body in the form of Shukradhatu Sarata because Shukradhatu is located in entire body. Shukra Sara person is known to possess unctuous (Snigdha), compact (Samhat) and white (Shweta) bones (Asthi), teeth (Danta), nails (Nakha), and children (Bahula Kamapraja). Shukra Dhatu is one of Pranayatanas of Sharira, from this information we can understand the importance of Shukradhatu. Therefore, this study was taken into consideration which has main objectives to review the concept of presence of Shukra Dhatu in the body without any sexual discrimination and its functions all over body.